1991
DOI: 10.1111/j.1439-0329.1991.tb01424.x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory evaluation of the efficacy of antiblue and biocide in the control of sapstain and mould fungi on Pinus elliottii

Abstract: Results of a test on the effects of Antiblue and Biocide at various concentrations and times of immersion on the growth sapstain and mould fungi are presented. Antiblue (active ingredient, sodium pentachlorophenate) was the better chemical providing com ete control at the lowest concentration of 1.5 %. Biocide, a chlorinated derivative and local suestitute for Antiblue, provided 55 control at 4 and 8 % concentrations and 74 % control at the highest concentration of 12 Yo. The time of immersion did not have a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Laboratory studies on the efficacy of Antiblue and Biocide T.T. against stain and mould fungi (Masuka, 1991) showed that a concentration of 1,5 per cent Antiblue was effective against tested fungi. The same concentration provided less protection in the field.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Laboratory studies on the efficacy of Antiblue and Biocide T.T. against stain and mould fungi (Masuka, 1991) showed that a concentration of 1,5 per cent Antiblue was effective against tested fungi. The same concentration provided less protection in the field.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…(an ammoniumbased chemical), in the control of sapstain and mould fungi. The results of those investigations, and causative fungi, are reported elsewhere (Masuka 1991(Masuka , 1992. Antisapstain chemicals were traditionally formulated for the prevention of stain and mould development in air-dried timber following sawing.…”
Section: Aj Masukamentioning
confidence: 99%
See 1 more Smart Citation